2017
DOI: 10.1016/j.celrep.2017.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Fork Head Regulates Nutrient Absorption and Promotes Longevity

Abstract: SummaryReduced activity of nutrient-sensing signaling networks can extend organismal lifespan, yet the underlying biology remains unclear. We show that the anti-aging effects of rapamycin and reduced intestinal insulin/insulin growth factor (IGF) signaling (IIS) require the Drosophila FoxA transcription factor homolog Fork Head (FKH). Intestinal FKH induction extends lifespan, highlighting a role for the gut. FKH binds to and is phosphorylated by AKT and Target of Rapamycin. Gut-specific FKH upregulation impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 66 publications
4
54
0
Order By: Relevance
“…It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/253542 doi: bioRxiv preprint first posted online Jan. 24, 2018; Our findings that IMD specifically affects insulin activity collaborate reports that the Drosophila TNFα homolog, Eiger, regulates production of insulin peptides in the brain (Agrawal et al, 2016), and that the FOXO homolog, Forkhead, regulates intestinal metabolism, and survival after infection in adult Drosophila (Bolukbasi et al, 2017). In addition, several studies identified interaction points between immune and insulin responses in the fly.…”
Section: Discussionsupporting
confidence: 65%
“…It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/253542 doi: bioRxiv preprint first posted online Jan. 24, 2018; Our findings that IMD specifically affects insulin activity collaborate reports that the Drosophila TNFα homolog, Eiger, regulates production of insulin peptides in the brain (Agrawal et al, 2016), and that the FOXO homolog, Forkhead, regulates intestinal metabolism, and survival after infection in adult Drosophila (Bolukbasi et al, 2017). In addition, several studies identified interaction points between immune and insulin responses in the fly.…”
Section: Discussionsupporting
confidence: 65%
“…It is not clear to what extent ISC division per se regulates lifespan; although it is certainly strongly linked with longevity (Biteau et al 2010;Rera et al 2011), recent studies have shown that homeostasis of differentiated cells is important for maintenance of gut function, including barrier function (Bolukbasi et al 2017;Resnik-Docampo et al 2016). Therefore, we analysed pathology of the epithelium, and barrier function of the intestine in 1x trametinib-treated flies over age.…”
Section: Trametinib Attenuates Age-related Intestinal Pathology and Lmentioning
confidence: 99%
“…A large and growing body of literature points to endocrine pathways being involved in nutrient perception and balance in order to coordinate organismal response to diet change. Nutrient sensing mechanisms and pathways are associated with aging and longevity from yeast to mammals [11][12][13][14], reviewed in [15][16][17][18][19]. The insulin/insulinlike signaling (IIS) together with the target of rapamycin (TOR) pathways are among the most studied pathways.…”
Section: Introductionmentioning
confidence: 99%